Menguak Tantangan dan Persiapan Konselor dalam Rangka Menuju Indonesia Emas 2045 - Silmy, Riza Aqilah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This research highlights the preparations and challenges counselors face in achieving the Vision of Golden Indonesia 2045. The focus on the basic skills required by counselors to provide effective services. Qualitative research methods and literature studies were used to explore counselors' perspectives and experiences regarding preparations and challenges towards Golden Indonesia 2045. The findings emphasize importance of quality education and training for counselors, as well as the integration of technology in counseling services. Future recommendations include enhancing collaboration between the government and educational institutions, strengthening supervision, and program evaluation to improve the quality of guidance and counseling services in Indonesia.